2008
DOI: 10.1088/0957-4484/19/30/305705
|View full text |Cite
|
Sign up to set email alerts
|

How flat is an air-cleaved mica surface?

Abstract: Muscovite mica is an important mineral that has become a standard substrate, due to its easy cleavage along the {001} planes, revealing a very flat surface that is compatible with many biological materials. Here we study mica surfaces by dynamic atomic force microscopy (AFM) operated in the non-contact mode (NC-AFM) under ultra-high vacuum (UHV) conditions. Surfaces produced by cleaving in UHV cannot be imaged with NC-AFM due to large surface charges; however, cleavage in air yields much less surface charge an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 33 publications
3
103
0
Order By: Relevance
“…Several previous studies [82; 135; 136; 138] were in agreement that the carbonaceous overlayer formed on cleaving mica in air could not be removed by exposure to UHV conditions. Ostendorf et al carried out a comparative AFM study of mica cleaved in air and in UHV, and found very different results with the two samples of different origin [141]. The surface cleaved in UHV could not be satisfactorily imaged in non-contact mode due to the magnitude of the surface potential, typically between -80 and -130 V. The potential could not be reduced by annealing in UHV, even at 560 K, but after a few minutes exposure to air the potential decreased to ±2.5 V. The subsequent AFM images revealed the presence of numerous particles on the surface, of lateral size in the range 1-5 nm, and the authors suggested that these were the K2CO3 crystallites previously observed by one of us [125].…”
Section: Surface Analytical Studies Of Air-cleaved and Vacuum-cleavedmentioning
confidence: 99%
“…Several previous studies [82; 135; 136; 138] were in agreement that the carbonaceous overlayer formed on cleaving mica in air could not be removed by exposure to UHV conditions. Ostendorf et al carried out a comparative AFM study of mica cleaved in air and in UHV, and found very different results with the two samples of different origin [141]. The surface cleaved in UHV could not be satisfactorily imaged in non-contact mode due to the magnitude of the surface potential, typically between -80 and -130 V. The potential could not be reduced by annealing in UHV, even at 560 K, but after a few minutes exposure to air the potential decreased to ±2.5 V. The subsequent AFM images revealed the presence of numerous particles on the surface, of lateral size in the range 1-5 nm, and the authors suggested that these were the K2CO3 crystallites previously observed by one of us [125].…”
Section: Surface Analytical Studies Of Air-cleaved and Vacuum-cleavedmentioning
confidence: 99%
“…Taylor and Schwartz [27] and Lim et al [28] have both used ex-situ AFM to study the films formed by fatty acid solution on alumina. Taylor and Schwartz studied film formation by octadecanoic acid from hexadecane.…”
Section: Afm Studies Of Carboxylic Acid Self-assemblymentioning
confidence: 99%
“…32 Moreover, the surface potential of mica cleaved under ultra high vacuum (UHV) conditions is up to two orders of magnitude higher than that for mica cleaved in air. 33 Therefore, we suppose that the strong charging of UHV-cleaved mica is associated with the presence of non uniformly distributed K + ions over the mica surface.…”
Section: B Surface Structuresmentioning
confidence: 99%